Digital and Social-Civic Skills in Future Primary Education Teachers: A Study from the Didactics of Social Sciences for the Improvement of Teacher Training in Competences - Rafael Guerrero Elecalde; Javier Contreras García; Antonio Luis Bonilla Martos; Begoña Serrano Arnáez (MDPI AG, 2024)
The use of technology, especially among young people, is providing new possibilities, including in the academic field, and requires teacher training through the development of skills and competences. At this point, Social Science Didactics plays a fundamental role, as it prepares future teachers to teach social knowledge in order to achieve useful and meaningful learning for students and society. Using an online questionnaire, structured with the Likert scale, which had previously been validated and published by Professors Peart, Gutiérrez-Esteban, and Cubo-Delgado, 156 students of the Degree in Primary Education of the subject Didactics of Social Sciences at the University of Granada (Spain) participated (academic year 2023-2024), with the aim of investigating the digital and socio-civic competences of trainee teachers in order to seek ways to improve their training. The results were processed in the IBM SPSS Statistics 25 programme, carrying out a descriptive statistical analysis, considering the mode and the variance ratio. The participating students mainly use digital environments to communicate with acquaintances and, although they know and value a democratic society, they do not exercise their citizenship on the Internet. This makes it even more necessary to train future teachers in digital competences, based on digital and socio-civic skills, as only in this way will they be able to train citizens capable of facing the challenges of the knowledge society.